The Use of Language in Product Advertising Discourse on Instagram - Qoiqotul Hikmah; Alvia Nuris sualalah; Ayyuhrimah (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study examines the use of language in product advertising discourse on the Instagram platform. With the rise of digital marketing, Instagram has become a strategic medium for product promotion. The focus of this study is to analyze the language style, persuasive rhetoric, and linguistic elements used by advertisers to attract attention, build brand image, and encourage purchasing decisions. Qualitative content analysis was applied to a sample of product advertisements from various categories. The results of the study indicate that advertisers on Instagram tend to use informal, emotive, and persuasive language supported by the use of metaphors, hyperbole, and direct appeals. These findings highlight how the characteristics of the Instagram platform influence linguistic communication strategies for advertising effectiveness.